Strategi Implementasi Program Open Defecation Free Melalui Penyediaan Jamban Sehat di Lingkungan Masyarakat Kecamatan Babakan Ciparay Kota Bandung - Choerunnisa, Raisa Rafifiti; Oktoviani, Rika (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2024)
This research was conducted in Babakan Ciparay District, Bandung City, with the aim of analyzing program implementation, analyzing program obstacles, and developing program strategies. According to WHO research, 81% of the population in ten countries practice open defecation. Indonesia being the second most populous country whose population defecates in the open. The Open Defecation Free program in Babakan Ciparay District has not been fully implemented due to limited land and the abundance of narrow alleys in the area. This research employs a qualitative method, with data collection techniques including interviews, field observations, and document studies.This research produces a strategy formulation based on the SWOT analysis technique. Research informant search method using purposive sampling. The research results show that the strengths include strong government policies, public outreach, and the development of health facilities. The weaknesses include low public knowledge and education levels, limited government budget, and a lack of supervisory personnel. The opportunities include monitoring by the district team, evaluation and monitoring efforts, and the provision of awards for communities that are 100% Open Defecation Free. To improve Open Defecation Free in Babakan Ciparay District, additional work programs need to be implemented in health centers and triggering locations. These programs include periodic education and increasing the number of Open Defecation Free areas. This initiative can be supported by posyandu cadres, nongovernmental organizations, village/ district officials, and healthcare organizations.